Different Clinical Presentation of Appendicolithiasis. The Report of Three Cases and Review of the Literature - Bulent Kaya; Cengiz Eris (SAGE Publishing, 2011)
An appendicolith is composed of firm feces and some mineral deposits. After increased use of abdominal computed tomography, appendicoliths are more frequently detected. Most of the patients with appendicolith are asymptomatic. However, an appendicolith may be associated with complicated appendicitis with serious outcomes. We reported three patients who exhibited different clinical symptoms due to appendicolithiasis. While one of the patients was confused with urolithiasis, the other two patients presented with phlegmenous and perforated appendicitis. We submit that appendicoliths may present different clinical findings and can mimic several pathologies including urinary disorders.